Factores de riesgo y su incidencia en esguince de tobillo en deportistas que acuden a la Federación Deportiva de Los Ríos periodo noviembre 2023- abril 2024. - Cevallos Quimbita, Melany Nicol (2024)
Practicing sports, whether professional or amateur, has the risk of suffering injuries, and among the most common is a sprained ankle, which has different degrees ranging from mild to severe. A sprained ankle is an injury resulting from a mechanism of action due to abnormal hyperextension of the movement of the ankle joint, may require only rest, therapeutic approach and sometimes immobilization with a splint or bandage. Regarding risk factors, they can be extrinsic and intrinsic, all of them are a group that influence the incidence of the injury. It is estimated that ankle sprains occur in about 10,000 people per day, and in the institution where the research takes place, the Los Ríos Sports Federation, it occurs in 75% of the people treated. Therefore, the general objective of the study is to determine the risk factors and their incidence of ankle sprains in athletes who attend the institution. The method to use is inductive, since it allows establishing risk factors by observing the characteristics of each patient. In conclusion, it can be said that knowing the risk factors reduces the incidence of having a sprain, especially in those who practice sports regularly.